Umphrofethi - Dlamini, Lu (UJ Press, 2026)
This translation by Lungile Dlamini is a timely gift of immeasurable proportions to her people. She is unequivocal in her offering, as articulated in her appeal to her readers: “Fundani le ncwadi, niyidlulisele nakwabanye njengesipho sengqondo nenhliziyo ejulayo ngomcabango".